Contractor selection of construction in a competitive environment - Zavadskas, Edmundas Kazimieras; Turskis, Zenonas; Tamošaitienė, Jolanta (Journal of Business Economics and Management, 2008)
Contractor selection is a vital part of the project management cycle and deals with risk and risk management. This paper presents contractors’ assessment and selection based on the multi‐attribute methods in a competitive and risky environment. The model is based on a multi‐attribute evaluation of contractors, the determination of their optimality criterion values according to Hodges‐Lehmann rule. The proposed model could be applied to assessment of construction operations. The attributes of contractor evaluation are selected taking into consideration the interests and goals of the stakeholders as well as factors that influence the process of construction efficiency. The model is based on metric scores. A background and a description of the proposed model are provided and a few key findings from the data analyses are presented.First published online: 14 Oct 2010